PENGEMBANGAN BAHAN AJAR PELUANG DENGAN PENDEKATAN KONTEKSTUAL BERORIENTASI PADA KEMAMPUAN PENALARAN DAN DISPOSISI MATEMATIS BERBASIS ANDROID - Karsoni Berta Dinata; Darwanto Darwanto (Eksponen, 2020)
Abstract: The purpose of this study is to produce a product in the form of opportunity teaching materials with a contextual approach oriented to mathematical reasoning and disposition abilities with an Android-based basis. Teaching material was developed using the development research (R&D) methodology. Teaching materials are validated, then tested on third semester students of the Mathematics Education Study Program at the University of Muhammadiyah Kotabumi Academic Year 2019/2010. Based on the results of the validation, an assessment is obtained from the side; 1) graphic design obtained a score of 153 in the very good category, 2) presentation of the material obtained a score of 129 was in the very good category, 3) the feasibility of the content obtained a score of 90 was in the very category, 4) Reasoning obtained a score of 37 which is in the good category because are in the interval of 30 ≤ S ≤ 38. Furthermore, based on the results of tests on students, an assessment of; 1) aspects of the display is obtained a score of 659 is in the good category, 2) aspects of the presentation of the material obtained by a score of 655 is in good, 3) aspects of the benefits obtained by a score of 1039 are in the good category. Thus it can be concluded that the teaching materials made have met the criteria of validity, practicality, and effectiveness